Diagnóstico dos sistemas de produção de mudas nativas do Vale do Ribeira - Silva, Francisca Alcivânia de Melo [UNESP]; Alfonsi, Leandro Garcia [UNESP]; Caceres, Danilo Pereira [UNESP]; Ferraz, Marcelo Vieira [UNESP]; Silva, Reginaldo Barboza da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
With the objective to make a diagnosis of nurseries of native seedlings of the 23 cities in the Ribeira Valley - SP were made visits to each municipality, applying a questionnaire with questions about infrastructure, size, legal compliance, labor-work, purchase of seeds, storage structures, documentation, quality of seedlings, among other things. 18 active nurseries have been identified. In municipalities that have nurseries it was found that the verified infrastructure is inadequate and the lack of knowledge about species, conditions and storage structure, treatment and harm cultural activity. The difficulty in marketing the seedlings reflects the lack of documentation, RENASEM and production control. The seedling production activity in the Ribeira Valley region has great potential for development, since there is availability of skilled labor and seed bank, but requires actions aimed mainly at technical guidance of producer and marketing support for that firm as an important sector within the supply chain of forest restoration in the state

Com o objetivo de fazer um diagnóstico da produção de mudas nos viveiros das 23 cidades do Vale do Ribeira – SP foram feitas visitas a cada município, aplicando-se um questionário, contendo perguntas sobre infraestrutura, tamanho, atendimento à legislação, mão-de-obra, aquisição de sementes, estruturas de armazenamento, documentação, qualidade das mudas, dentre outros aspectos. Foram identificados 18 viveiros ativos. Nos municípios que possuem viveiros constatou-se que a infraestrutura verificada é insuficiente e a falta de conhecimento sobre espécies, condições e estrutura de armazenamento, tratos e culturais prejudicam a atividade. A dificuldade na comercialização das mudas é reflexo da falta de documentação, RENASEM e controle da produção. A atividade de produção de mudas na região do Vale do Ribeira tem grande potencial para desenvolvimento, uma vez que há disponibilidade de mão-de-obra e banco de sementes, porém necessita de ações voltadas principalmente à orientação técnica do produtor e apoio à comercialização para que se firme como setor importante dentro da cadeia produtiva da restauração florestal no Estado.
Keywords: Nurseries; Productive chain; Forest species; Viveiros; Cadeia produtiva; Essências florestais